Árion: A Blockchain Framework for Traceability in Supply Chain Management - Mascarenhas Junior, Edivaldo; Carvalho Neto, Manoel; Freitas, Allan Edgard (Workshop em Blockchain: Teoria, Tecnologias e Aplicações (WBlockchain), 2020)
A complex web of relationships provides goods for manufacturing, assembling, and delivering final products known as the supply chain. Emerging technologies have been used in supply chain systems in order to provide traceability. However, these systems tend to be centralized, monopolistic, and asymmetric. As a consequence, they may result in trusting problems, such as fraud, corruption, and tampering. Blockchain technology provides a new approach for information systems based on decentralization, that can apply for supply chain systems. This work presents a Blockchain-based framework for developing applications that provide such traceability for supply chain management.